2023
DOI: 10.3390/biomedicines11051314
|View full text |Cite
|
Sign up to set email alerts
|

Spheroid Culture System, a Promising Method for Chondrogenic Differentiation of Dental Mesenchymal Stem Cells

Abstract: The objective of the present work was to develop a three-dimensional culture model to evaluate, in a short period of time, cartilage tissue engineering protocols. The spheroids were compared with the gold standard pellet culture. The dental mesenchymal stem cell lines were from pulp and periodontal ligament. The evaluation used RT-qPCR and Alcian Blue staining of the cartilage matrix. This study showed that the spheroid model allowed for obtaining greater fluctuations of the chondrogenesis markers than for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…This research aimed to determine the ‘ideal’ source of MSCs for cartilage tissue engineering, which is ongoing, and various types of MSCs were shown to assist in articular cartilage repair. Mélou et al, using adult dental pulp MSCs, demonstrated that a spheroid model ensures higher expression of chondrogenesis markers compared to monolayer or pellet culture [ 21 ]. By reviewing the reported clinical trials, Peng et al found that osteoarthritis cell-based therapy translational research is mostly limited to bone marrow-derived MSCs (BMMSCs), ATMSCs, and WJMSCs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research aimed to determine the ‘ideal’ source of MSCs for cartilage tissue engineering, which is ongoing, and various types of MSCs were shown to assist in articular cartilage repair. Mélou et al, using adult dental pulp MSCs, demonstrated that a spheroid model ensures higher expression of chondrogenesis markers compared to monolayer or pellet culture [ 21 ]. By reviewing the reported clinical trials, Peng et al found that osteoarthritis cell-based therapy translational research is mostly limited to bone marrow-derived MSCs (BMMSCs), ATMSCs, and WJMSCs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%